ANALISIS PENGENDALIAN KUALITAS PRODUK BATAKO DI UKM CETAK BATAKO SOBIRIN - Alfajri, Muhammad; Aji Prasetyo, Bahariandi (Computer Science and Industrial Engineering, 2025)
The increase in the need for building materials must also be accompanied by an increase in the quality of these building materials. One of the building materialsthat is often used in building and housing construction is brick. The purpose of this stury is to determine the results of quality control of brick products using six sigma in reducing product defects in UKM Print Batako Sobirin. Quantitative results of DPMO and Sigma level calculations are carried out in each production year. Furthermore, the process DPMO is obtained in brick production year. Furthermore, the process DPMO is obtained in brik production with an average of 333333 defects. This means that the number of defects that may occur in every million units of poduct is 333333 units. The brick production process is at level 5, namely 1.934 sigma (in the category 233 defects – 233 defects – 6,210 defects). The process carried out still needs to be controlled and improved continuously in order to obtain a decreasing DPMO pattern ad a Sigma level pattern that increases over time to reach level 6 sigma. DMAIC imporvements are focused on the process starting with the preparation of the place, tools, and materials, followed by milling, molding drying, and testing the compressive strength of the bricks. Consequently,during the post-improvement phase (April-June 2025),the defect rate dropped to an average of 5,5%. Therefore,the application of DMAIC in the Sobirin Brick Making SME can be deemed successful in lowering product defect levels,though additional control is needed to reach optimal results.